Toward a formal definition of water scarcity in natural‐human systems. Issue 7 (8th July 2013) - Jaeger, W. K.; Plantinga, A. J.; Chang, H.; Dello, K.; Grant, G.; Hulse, D.; McDonnell, J. J.; Lancaster, S.; Moradkhani, H.; Morzillo, A. T.; Mote, P.; Nolin, A.; et al.
<x xml:space="preserve">Abstract</x> [1] Water scarcity may appear to be a simple concept, but it can be difficult to apply to complex natural‐human systems. While aggregate scarcity indices are straightforward to compute, they do not adequately represent the spatial and temporal variations in water scarcity that arise from complex systems interactions. The uncertain effects of future climate change on water scarcity add to the need for clarity on the concept of water scarcity. Starting with a simple but robust definition—the marginal value of a unit of water we—highlight key aspects of water scarcity and illustrate its many biophysical and socioeconomic determinants. We make four central observations. First, water scarcity varies greatly across location, time, and a multitude of uses that are valued either directly or indirectly by society. Second, water scarcity is fundamentally a normative, anthropocentric concept and, thus, can and should be distinguished from the related, purely descriptive notion of water deficit. While such an anthropocentric perspective may seem limiting, it has the potential to encompass the vast range of interests that society has in water. Third, our ability to understand and anticipate changes in water scarcity requires distinguishing between the factors that affect the value or benefits of water from those affecting the costs of transforming water in space, time and form. Finally, this robust and rigorous definition of water scarcity will facilitate better communication and understanding for both policymakers and scientists.